Effects of mass energy and line mass on characteristics of the direct laser fabrication parts. Issue 2 (12th March 2018) - Wang, Xinlin; Deng, Dewei; Zhang, Hongchao
Abstract : Purpose: This study aims to investigate the effects of mass energy and line mass on the geometrical dimensions, microstructures, hardness and mechanical properties of direct laser fabrication parts. Design/methodology/approach: Direct laser fabrication is successfully used to manufacture a series of samples of AISI 316L stainless steel. Findings: The width and height of the deposition layers increase with increasing mass energy and line mass. When the powder feed rate is 0.295 g/s, higher mass energy and line mass create more refined grains. However, mass energy and line mass have adverse effects on grain size at the powder feed rate of 0.241 or 0.187 g/s. Higher ultimate tensile strength (UTS) values and reduced ductility values are obtained in comparison with those obtained by traditional methods. Thus, the increase in the mass energy and line mass improves the mechanical properties of the parts. Originality/value: This study is helpful for the optimization of the parameters in the direct laser fabrication process.